Internalisasi Nilai Religius pada Mata Pelajaran PAI Jenjang SD untuk Mengembangkan Sikap Keberagamaan Siswa - Nurdiyanto, Nurdiyanto; Hasan Basri, Hasan Basri; Andewi Suhartini, Andewi Suhartini (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2024)
The aim of this research is to describe religious values in PAI subjects at the elementary school level and to analyze the concept of religious values in PAI subjects at the elementary school level to develop students' religious attitudes. The approach taken in this research uses a qualitative approach with the library research method. Namely, research based on a study of writings or literature relevant to the research. The data collection technique in this research collects primary and secondary data. Primary data includes books, e-books, and scientific journals. Meanwhile, secondary data from supporting data includes online proceedings, magazines, and newspapers related to the research theme (Wong et al., 2014). While the analysis technique carried out uses descriptive narrative analysis, namely categorizing data, reading memory, classifying data, interpreting data, and presenting data (Creswell, 2002). Meanwhile, the results of this research are learning methods in PAI, development of religious attitudes, PAI at the elementary school level, religious values in PAI, PAI evaluation, the role of PAI teachers, and the influence of internalization of religious values on students. The conclusion of this article shows that it is important to instill religious values in elementary school students such as elementary school. The points contained in the PAI subject are in harmony and in line with the formation of students' character, especially in developing their religious attitudes, because in reality elementary school children are called concrete operationalists where children are still free from dirty words or are identical, more so by seeing and hearing what they say—given him a stimulus. So, if elementary school children develop their religious attitudes, it will be very influential in continuing their growth and development at the advanced level.